2021
DOI: 10.3390/su132011301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Communication on Capital Project Performance: A Mediated Moderation Model

Abstract: Many studies demonstrate the importance of communication in project performance. However, little is known about how project communication exerts its effects on the outcomes of capital projects that have a large impact on environmental and economic sustainability. Using a longitudinal survey and bootstrap-based structural-equation modeling, this study uncovers how project competencies and team innovative behavior affect the relationship between project communication and capital project performance. This study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Specifically, this study advances the understanding of the moderating effect that CB plays in the relationship between KSBs and KM. Previous studies (Chen, 2021; Chi et al. , 2021; Kwofie et al.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Specifically, this study advances the understanding of the moderating effect that CB plays in the relationship between KSBs and KM. Previous studies (Chen, 2021; Chi et al. , 2021; Kwofie et al.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, this study advances the understanding of the moderating effect that CB plays in the relationship between KSBs and KM. Previous studies (Chen, 2021;Chi et al, 2021;Kwofie et al, 2021;Mueller, 2012) explores the positive influence of communication on knowledge sharing; however, as far as we know there is a lack of studies exploring the CBs moderating role. This study support that, despite the direct effect of CBs in KM are not significant, the moderating role played in the relationship between KSB and CB is significant and negative, as expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the positive relationship between project technological capacity and project performance turns stronger when team creativity weakens. One possible explanation is that project technological capacity and team creativity do not have a linear relationship; rather it is curvilinear such as an inverted u-shaped relationship (Chen, 2021).…”
Section: Table 2: Bootstrap-based Methods For Testing the Moderating ...mentioning
confidence: 99%
“…In other words, we argue that project technological capacity has a stronger positive impact on project performance when team creativity is stronger. Moreover, the importance of creativity for organizational competitiveness and efficiency is widely recognized, and creative behavior has become an important corporate asset in business environments characterized by ever-increasing competition (Chen, 2021;Ng & Lucianetti, 2016).For example, Romero and Martínez-Román (2012) state the important effects of employee creative behavior in the early stages of small business conception and development on their following economic outcomes. They showed that employee education and training are key determinants of creativity.…”
Section: Research Hypothesesmentioning
confidence: 99%